Nonlinear eddy viscosity modeling and experimental study of jet spreading rates. (13th June 2013) - Heschl, C.; Inthavong, K.; Sanz, W.; Tu, J.
Abstract Indoor airflow pattern is strongly influenced by turbulent shear and turbulent normal stresses that are responsible for entrainment effects and turbulence‐driven secondary motion. Therefore, an accurate prediction of room airflows requires reliable modeling of these turbulent quantities. The most widely used turbulence models include RANS‐based models that provide quick solutions but are known to fail in turbulent free shear and wall‐affected flows. In order to cope with this deficiency, this study presents a nonlinear k‐ε turbulence model and evaluates it along with linear k‐ε models for an indoor isothermal linear diffuser jet flow measured in two model rooms using PIV. The results show that the flow contains a free jet near the inlet region and a wall‐affected region downstream where the jet is pushed toward the ceiling by entrainment through the well‐known Coanda effect. The CFD results show that an accurate prediction of the entrainment process is very important and that the nonlinear eddy viscosity model is able to predict the turbulence‐driven secondary motions. Furthermore, turbulence models that are calibrated for high Reynolds free shear layer flows were not able to reproduce the measured velocity distributions, and it is suggested that the model constants of turbulence models should be adjusted before they are used for room airflow simulations.